Effect of formulation variables on cis-platin loaded chitosan microsphere properties - (:unkn) unknown (TAYLOR & FRANCIS LTD, 1999)
Chitosan microspheres containing cis-platin were prepared using a w/o emulsion system. Variables important for microsphere properties were investigated: these include; chitosan, cis-platin and glutaraldehyde concentrations, the types of chitosan and oil, the cross-linking process and stirring rate. Chitosan and glutaraldehyde concentrations, the types of oil and chitosan have a significant effect on cis-platin entrapment in chitosan microspheres. In general, incorporation efficiency was high and ranged from 28-99%. The type and concentration of chitosan affected cis-platin release from microspheres. The type of oil was also important for release properties. Cis-platin release from microspheres is characterized by an initial burst effect.
Keywords: cis-platin; chitosan; microspheres; controlled-release; RELEASE CHARACTERISTICS; CISPLATIN; CHEMOEMBOLIZATION